Letter (copy) : Help for the Spanish Workers - Tewson, Vincent
028-0186-001 Our Ref: HVT/FC/30. 22nd September, 1936. Mr. J. Marchbank, Unity House, Euston Road, N.W.1. Dear Mr. Marchbank, HELP FOR THE SPANISH WORKERS. Referring to your letter (reference F.M.A.2) which arrived here this morning, together with enclosures from the International Transportworkers' Federation, Mr. Hicks is going to Paris this weekend for a meeting of the General Council of the I.F.T.U., and I am raising with him the subject of your letter in order that upon his return I may be able to send you more definite information than is at present available. I am, however, surprised to learn of the report that the workers in Madrid know nothing of the assistance which has been rendered by our Fund. I will write you again early next week. Yours sincerely, for Joint Secretary. 292/946/28/186